Perancangan dan Penerapan Sistem Informasi Kenotariatan Menggunakan Bahasa Pemrograman PHP - Muhammad Ichsan Adhiim; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Notary is a judicial officer who is authorized to make an authentic deed and agreements of individuals, institutions, or land properties. In the daily work, Notary records customer data and work data. However, the result of recording data manually makes Notary overwhelmed in data processing, causing task completion time becomes longer. The Notary Information System is designed using Waterfall methodology using PHP programming language, Code Igniter framework, and MySQL database. Analysis of system requirements is is conducted by interviewing the Notary, so the design is appropriate and well targeted. This research produces an information system that is capable of recording type of work data, customer data, land, property data, employment data, income and outcome data, and data revenue recapitulation in the form of text and graphics data. This information system design also has an additional functions that notifies the clients about the completed work via E-mail and SMS. This information system design was tested using the black box method, and the results of these tests indicate that all functions in the system have been running well.